IDIOLEKT AND IDIOUSLUB'S ANALYSIS FROM THE POINT OF VIEW OF LITERARY GENRES - Nilufar Yokubovna Turdiyeva (Western European Studies, 2023)
This article covers the issues of idiolekt, which is a comprehensive direction in modern literature, and its giving in poetic text, raises the issue of idiostilistic bilingualism and considers the main characteristics of each of these methods of organizing speech.
Keywords: idiolekt; idiouslub; literary genre; image